Respuesta :

Answer:

[tex]a=\dfrac{3b-7}{3}[/tex]

Step-by-step explanation:

Given that,

The given equation is :

5b + 6a – 7 = 2b + 9a

We need to solve the above equation for a. Taking he terms having a and b in LHS and constants in RHS.

5b+6a-2b-9a=7

taking like terms together

(6a-9a)+(5b-2b)=7

-3a+3b=7

Subtracting both sides by 3b. So,

-3a+3b-3b=7-3b

-3a=7-3b

Dioviding both sides by (-3). So,

[tex]a=\dfrac{7-3b}{-3}\\\\a=\dfrac{3b-7}{3}[/tex]

Hence, the value of a is [tex]a=\dfrac{3b-7}{3}[/tex].

ACCESS MORE